TEACHERS’ REINFORCEMENT AND STUDENTS’ PERCEPTION ON ENGLISH LANGUAGE SUBJECT - Nika Nurdiana; Andi Tenri Tampa; Syamsiarna Nappu (Universitas Muhammadiyah Makassar, 2021)
This study aims to determine the types of reinforcement that the teachers use in the classroom as well as students’ perceptions of teachers’ reinforcement when teaching English in the classroom. This research is a qualitative design. It describes the reinforcement used by English teachers and the students’ perception, as well. There are three instruments to obtain the data, namely; observation, questionnaire, and interview. Observation is used to see teachers’ reinforcement and students’ response when the teachers use reinforcement, the questionnaire is to see and get more information about students’ perception towards teachers’ reinforcement in teaching English, while the interview is used to see the types of teachers’ reinforcement in the classroom activities. All the data are processed and presented in a descriptive form to ease the readers to get complete information about the research results. The findings show that teachers’ reinforcement in the classroom influence the students’ response. It means that students’ responses and perceptions will depend on the types of reinforcement used by the teachers. Then, it can be concluded that the more positive the teachers’ reinforcement, the more positive and the better the students’ response, and perception will be.